2010
DOI: 10.1159/000319773
|View full text |Cite
|
Sign up to set email alerts
|

Little Association between Intracranial Arterial Stenosis and Lacunar Stroke

Abstract: Atheromatous middle cerebral artery (MCA) stenosis could cause lacunar stroke by occluding lenticulostriate artery origins, but atheroma is common, and previous studies lacked suitable controls. We aimed to determine if intracranial atheroma was more common in lacunar than in cortical ischaemic stroke. We recruited patients with lacunar stroke and controls with mild cortical stroke, confirmed the stroke subtype with magnetic resonance imaging and used transcranial Doppler ultrasound imaging to record flow velo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 53 publications
1
27
1
1
Order By: Relevance
“…Several studies have suggested that MCA stenosis obliterating the mouth of deep perforating arteries is one of the mechanisms of perforating artery infarcts [21,22,23,24]. On the other hand, Wardlaw et al [25] reported that intracranial large artery atheroma is unlikely to be a common cause of lacunar infarcts. Cho et al [26] did not find the difference between infarct size and MCA disease in patients with acute deep subcortical MCA territory infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that MCA stenosis obliterating the mouth of deep perforating arteries is one of the mechanisms of perforating artery infarcts [21,22,23,24]. On the other hand, Wardlaw et al [25] reported that intracranial large artery atheroma is unlikely to be a common cause of lacunar infarcts. Cho et al [26] did not find the difference between infarct size and MCA disease in patients with acute deep subcortical MCA territory infarcts.…”
Section: Discussionmentioning
confidence: 99%
“…В то же время часть выявленных взаимосвязей (с фракцией вы-броса и степенью стеноза) указывает на важную роль гипо-перфузии в патогенезе ЦБМС, что соотносится с недавно предложенной I. Masafumi и Y. Yamamoto концепцией, сог-ласно которой важным звеном в патогенезе ЦБМС являет-ся дисфункция гематоэнцефалического барьера, которая вызывается, в частности, гипоперфузией на фоне атеро-склероза крупных церебральных артерий [11]. Тем не менее существует противоположная точка зрения, в соответствии с которой старение и лейкоареоз сопровождаются потерей вещества мозга, что приводит к уменьшению потребности в его перфузии [12].…”
Section: о р и г и н а л ь н ы е и с с л е д о в а н и я и м е т о д unclassified
“…6 Yet a host of postmortem and imaging studies implicate MCA atherosclerosis as a likely cause of stroke. [7][8][9] Further investigation is necessary to evaluate the prevalence and importance of MCA disease as an etiology of ischemic injury.…”
mentioning
confidence: 99%